Feasibility study of enhanced biogenic coalbed methane production by super-critical CO2 extraction. (1st January 2021) - Guo, Hongguang; Zhang, Yujie; Zhang, Yiwen; Li, Xingfeng; Li, Zhigang; Liang, Weiguo; Huang, Zaixing; Urynowicz, Michael; Ali, Muhammad Ishtiaq
Abstract: Super-critical CO2 enhanced coalbed methane (Sc-CO2 -ECBM) and microbially enhanced coalbed methane (MECBM) are environment-friendly technologies that can improve CBM recovery and generation. In this study, a new approach of MECBM based on Sc-CO2 extraction is presented. The Sc-CO2 pretreatment experiments of anthracite and bituminous coal were conducted to produce biomethane. The extracted organics and the changes of coal structure caused by Sc-CO2 were also analyzed to discuss the mechanism of methane stimulation. The results indicated that methane yields have been greatly improved after Sc-CO2 extraction by 734.85% and 148.15% for anthracite and bituminous coal, respectively. The extractions observed by GC-MS analysis is also favored to generate methane by microorganisms. The little increment of methane production from coal treated by subcritical CO2 indicated that the special characteristics of Sc-CO2 were critical for the stimulation of methane production. More functional groups and even new functional groups were formed to increase coal bioavailability after Sc-CO2 extraction. The specific surface area and total pore volume of bituminous coal increase after Sc-CO2 extraction that could provide more action sites for microorganisms and enzymes. These results strongly proved the feasibility of enhancing CBM by microbial degradation based on Sc-CO2 extraction. Highlights: A new approach of MECBM based on Sc-CO2 extraction was presented and verified. 734.85% and 148.15% of methane increment was observed for anthracite and bituminous coal. The characteristics of Sc-CO2 were critical for the stimulation of methane production. A mechanism of enhancing methane production by Sc-CO2 extraction was proposed.